2016
DOI: 10.18632/oncotarget.11651
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SHCBP1 as a novel downstream target gene of SS18-SSX1 and its functional analysis in progression of synovial sarcoma

Abstract: The SS18-SSX1 fusion gene has been shown to play important roles in the development of synovial sarcoma (SS), but the underlying molecular mechanisms and its downstream target genes are still not clear. Here SHC SH2-domain binding protein 1 (SHCBP1) was identified and validated to be a novel downstream target gene of SS18-SSX1 by using microarray assay, quantitative real-time (qPCR) and western blot. Expression of SHCBP1 was firstly confirmed in SS cell line and SS tissues. The effects of SHCBP1 overexpression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 43 publications
(52 reference statements)
1
32
0
Order By: Relevance
“…Knockdown of SHCBP1 significantly decreased p-AKT expression, but not total AKT levels, in synovial sarcoma cells. 31 Additionally, Chen et al reported that silencing SHCBP1 in mouse neuroectodermal stem cells markedly decreased the level of p-AKT in the presence of FGF2. 32…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of SHCBP1 significantly decreased p-AKT expression, but not total AKT levels, in synovial sarcoma cells. 31 Additionally, Chen et al reported that silencing SHCBP1 in mouse neuroectodermal stem cells markedly decreased the level of p-AKT in the presence of FGF2. 32…”
Section: Discussionmentioning
confidence: 99%
“…Lentiviral vectors for BMP-7 overexpression. pgcl-green fluorescent protein (GFP)-lentivirus carrying a full-length human BMP-7 cDnA sequence (Lv-BMP-7) and a non-targeting sequence (Lv-Control) were synthesized by Shanghai GeneChem Co., Ltd. Lentivirus packaging and infection were performed as described previously (21). One day before transfection, 1.2x10 7 HEK 293T cells were plated at 90-95% confluence (in 15-cm dishes).…”
Section: Methodsmentioning
confidence: 99%
“…For depletion of FLVCR1, a human FLVCR1-targeting shRNA sequence was cloned into pGCSIL-green fluorescent protein (GFP) vector to generate pGCSIL-GFP-FLVCR1-RNAi, with target sequence 5'-CCC TGAAGAGTACTCCTATAA-3' (synthesized by Shanghai GeneChem Co., Ltd., Shanghai, China), or control scrambled shRNA (Lv-shCon sequence, 5'-TTCTCCGAACGTGTCA CGT-3'). Lentiviruses production and infection were performed as previously reported (7). Stable cell lines (SW982 and HS-SY-II) expressing FLVCR1 shRNAs were selected for 10 days with 0.5 µg/ml puromycin.…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting. Standard western blot assays were performed as described previously (7,23). Briefly, cells were harvested in the NE-PER™ Nuclear and Cytoplasmic Extraction Reagents (cat.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation